2016
DOI: 10.1155/2016/8243095
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Health Information on the Internet for Urolithiasis on the Google Search Engine

Abstract: Purpose. To compare the quality of health information on the Internet for keywords related to urolithiasis, to assess for difference in information quality across four main Western languages, and to compare the source of sponsorship in these websites. Methods. Health On the Net (HON) Foundation principles were utilised to determine quality information. Fifteen keywords related to urolithiasis were searched on the Google search engine. The first 150 websites were assessed against the HON principles and the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Less than 1 in 13 websites in this study were accredited by the HON Foundation. This mirrors findings in studies relating to urological conditions, 11,14 with higher rates reported in oncologic studies. 10,13 Although the low rate of HON-accredited websites is concerning, we found that topranking results had a significantly higher rate of HON accreditation, reaching one-third of first search result websites.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Less than 1 in 13 websites in this study were accredited by the HON Foundation. This mirrors findings in studies relating to urological conditions, 11,14 with higher rates reported in oncologic studies. 10,13 Although the low rate of HON-accredited websites is concerning, we found that topranking results had a significantly higher rate of HON accreditation, reaching one-third of first search result websites.…”
Section: Discussionsupporting
confidence: 85%
“…This mirrors findings in other studies. 11 Although we had concerns initially that marketing and commercial interests could bias the available health information, we found the majority of commercially-sponsored HON-accredited websites to be large private hospital networks and commercial health information networks, rather than manufacturers and service marketing. These large firms employ large managerial and editorial teams to ensure correct accreditation of their websites, contrasting with government and education agencies, which often rely on their brand name and sponsorship status to support their impartiality and authority.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…DISCERN consists of 15 key questions plus an overall quality rating. Each question represents a separate quality criterion [13]. The 8-point HONcode assesses the following principles: authority, complementarity, privacy, attribution, justifiability, transparency, financial disclosure, and advertising policy [14].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of analyzing search engine results, this field is divided into two areas. First, researchers are evaluating organic results displayed by search engines with tools that are widely used today such as HONcode [13], the Journal of the American Medical Association (JAMA) benchmarks, and the DISCERN tool [14], and scales such as Flesch-Kincaid reading level and Flesch reading ease [14]. Results from Google are downloaded and evaluated [16] with regard to how they answer health questions [17], for example, from parents on neonatal intensive care [18], or on palliative care [19] or human papillomavirus vaccination [20]; and there are large systematic reviews of autoimmune diseases [21].…”
Section: Introductionmentioning
confidence: 99%